An examination of works for wind band and brass ensemble: Toccata for band by Frank Erickson, Mutations from Bach by Samuel Barber, and Nobles of the Mystic Shrine by John Philip Sousa - Ladd, Adam Richard (Kansas State University, 2014)
The following report is a comprehensive analysis of two works for wind band and one work for brass ensemble, prepared by Adam Ladd. The report was completed during the Spring semester of 2014 and culminated with live performances of each piece by the Kansas State University Concert Band and Brass Ensemble with Adam Ladd conducting. Audio and video recordings of the conducted performances can be found within the K-State Research Exchange database. The following report includes three comprehensive Unit Studies or Teacher Research Guides in the format that is described in the Teaching Music Through Performance in Band book series. The report also includes three Tracz Analysis Grids in the format that is found in The Art of Interpretation of Band Music. The examined pieces are as follows. Toccatta for Band, by Frank Erickson, Mutations from Bach, by Samuel Barber, and Nobles of the Mystic Shrine, by John Philip Sousa, arranged by Philip Sparke.
Keywords: Conducting; Analysis; Samuel Barber; Frank Erickson; John Philip Sousa; Music (0413)